Unnatural Deaths in Brazilian Children and Adolescents - Leite Cavalcanti, Alessandro; Batista Sarmento de Oliveira, Thaliny; Sant´Anna Araújo Rodrigues, Iris; Leite Cavalcanti, Christiane; Sarmento Batista de Oliveira, Thaisy; Cabral Cavalcanti, Alidianne Fabia (O Mundo da Saúde, 2018)
Accidents and violence are considered an important public health problem for being the main cause of mortality among children and adolescents. Assuming the hypothesis that the deaths predominantly affect men, victims of traffic accidents, the aim of this study was to assess unnatural deaths in Brazilian children and adolescents in a city in northeastern Brazil. A cross-sectional study was carried out with analysis of 584 forensic medical reports from the Legal Medicine Institute of Campina Grande, Brazil, between January 2008 and December 2011. Descriptive and inferential statistical analysis was conducted using the chi-square test (a = 0.05). Victims were mostly males (82.4 %) and adolescents aged from 15 to 19 years (70.0 %). The main causes of unnatural deaths were aggressions (39.2 %), followed by traffic accidents (32.7 %). Significant associations between etiology and age group were observed (p<0.001), indicating high percentages of deaths due to aggressions (34.9 %) and traffic accidents (22.94 %) within the age group 15-19 years, etiology and gender of the victim (p<0.001) and type of traffic accident and victim’s age (p < 0.001). With regard to traffic accidents, there were more records of accidents involving motorcyclists (46.7 %), followed by vehicle occupants (29.8 %) and pedestrians (15.7%). Our hypothesis was confirmed, and the aggressions and traffic accidents were the most common causes of unnatural deaths, primarily affecting males aged from 15 to 19 years. Most deaths from traffic accidents involved motorcycle accidents.